Life-threatening arrhythmia in patients with suspected acute myocarditis - Melina Krempke; Jasmin Büchel; Kseniya Bulatova; Gianmarco M. Balestra; Philip Haaf; Jeanne Pouly; Paul Drews; Christian Mueller; Sven Knecht; Patrick Badertscher; Felix Mahfoud; Michael Kühne; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: Patients with acute myocarditis (AM) often undergo prolonged rhythm monitoring due to the risk for life-threatening arrhythmia. Objective: To describe the occurrence, timing and potential early rule-out of life-threatening arrhythmia in patients with AM. Methods: We included consecutive patients with suspected AM admitted to the ICU/IMC for continuous rhythm monitoring into a cohort study. We assessed the incidence and timing of life-threatening arrhythmia (sustained ventricular tachycardia, ventricular fibrillation, cardiac arrest). To rule-out arrhythmia, we evaluated left ventricular ejection fraction (LVEF), maximal cardiac troponin-T (cTnT) levels and a multivariable model. Results: Among 304 patients with AM (41 ± 16.6 years, 27 % female), 13 life-threatening arrhythmias occurred in 10 (3.3 %) patients. Of these, 8 occurred within 24 h, 2 between 24–48 h and 3 after 72 h of hospitalization. Patients with life-threatening arrhythmia had substantially higher mortality rates (40 % vs. 0.3 %, p < 0.001). There was no binary cut-off for LVEF and cTnT to rule-out arrhythmia. The last life-threatening arrhythmia occurred before the cTnT-peak in 3 (42.9 %), simultaneously with the peak in 1 (14.3 %), and after the peak in 3 (42.9 %) patients. The final multivariable model included female sex, cTnT, and LVEF and demonstrated an area under the curve of 0.98 (95 % CI 0.96–1), with a sensitivity of 99 % and specificity of 75 % to rule-out life-threatening arrhythmia. Conclusions: In patients with suspected AM, life-threatening arrhythmias were rare but associated with a 40% mortality rate. A combined model including 3 clinical variables ruled-out life-threatening arrhythmia with a high sensitivity and may help to guide the indication of rhythm monitoring.